Study of clinical profile of acute respiratory distress syndrome in pneumonia and outcome in intensive care unit - Deshmukh, Aniket; Paritekar, Anita (International Journal of Research in Medical Sciences, 2024)
Background: ARDS is a progressive inflammatory lung injury in patients with hypoxemic respiratory failure. Aspiration pneumonia and pneumonia are the most common cause of ARDS in direct lung injury whereas sepsis is the most common cause of ARDS in Indirect lung injury. Methods: This was observational study conducted in Intensive care unit, Department of Medicine, CPR Hospital, Kolhapur, Maharashtra for 6 months from 1 June to 30 November 2023 in 41 patients. Results: Most common cause of ARDS secondary to pneumonia, in this study population is bacterial pneumonia, followed by viral and parasitic infections. Average day of hospital stay for bacterial pneumonia is 13 days and 11 and 10 days for viral and parasitic infections respectively. For bacterial pneumonia mortality was 36%, for viral pneumonia was 37% and parasitic pneumonia was 33.33%. Out of 41 patients,16 patients were in mild ARDS with the SOFA score range of 2 to 5 and 12 patients were in moderate ARDS with SOFA score range of 6 to 9 and 12 patients were in severe ARDS with SOFA score range of 12 to 14. Conclusions: With our study we would like to conclude that sofa score is a good predictor of mortality in c/o ARDS patients in ICU setting. Patients who had sofa score of equal or more than 9 and who were in the category of moderate to severe ARDS, had poorer outcomes and high mortality rate.